2017
DOI: 10.1021/acs.jpcc.7b04165
|View full text |Cite
|
Sign up to set email alerts
|

Phase Retransformation and Void Evolution of Previously Heated HMX-Based Plastic-Bonded Explosive in Wet Air

Abstract: Octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocinebased plastic-bonded explosive (HMX-based PBX) is one of the most important solid energetic materials. The properties of HMX-based PBX are significantly affected by defects, which were reported recently to be generated during the postheating storage. However, the related mechanism is not well understood. In the study, with the in situ X-ray diffraction and small-angle neutron scattering, we explored the phase retransform and void evolution of previously heated HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Apart from chemical components, crystal properties, including phase structures, grain sizes, and surface and internal defects, are known to have a significant influence on the mechanical strength, sensitivity, and stability of high explosives. HMX (octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) is an eight-membered heterocyclic high-energy explosive that has been widely used for military weapons, aerospace applications, and modern industrial applications because of its characteristics of high energy density, good thermal stability, high detonation performance, and product cleanliness. By controlling the crystallization rate in the solution, we can observe four crystal structures, including three pure crystallization phases of α, β, and γ and a hydrate γ structure, at ambient conditions. The β phase is the most thermodynamically stable polymorph that has the highest density and is the only one used in weapons.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from chemical components, crystal properties, including phase structures, grain sizes, and surface and internal defects, are known to have a significant influence on the mechanical strength, sensitivity, and stability of high explosives. HMX (octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) is an eight-membered heterocyclic high-energy explosive that has been widely used for military weapons, aerospace applications, and modern industrial applications because of its characteristics of high energy density, good thermal stability, high detonation performance, and product cleanliness. By controlling the crystallization rate in the solution, we can observe four crystal structures, including three pure crystallization phases of α, β, and γ and a hydrate γ structure, at ambient conditions. The β phase is the most thermodynamically stable polymorph that has the highest density and is the only one used in weapons.…”
Section: Introductionmentioning
confidence: 99%
“…Solid–solid polymorphic transitions ubiquitously exist in organic and inorganic crystals related to photoelectric materials, , pharmaceuticals, and energetic materials . Since the properties of materials could be significantly changed accompanied by the polymorphic transition, understanding how the phase transforms and how to stabilize the phase form are fundamental questions in the research field correlated with polymorphic crystals. , Various reports have demonstrated that the polymorphic transition can be tuned through substitution of some ions or doping with other particular ions. However, this strategy is not suitable for organic molecular crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The phase before and after heating was identified by neutron diffraction. Because water can accelerate the δ- to β-HMX retransformation, two parallel experiments were designed to evaluate if any different processes exist in dry and humid circumstance. HMX-d8 (2.5 g; hereafter named sample 1#) was directly put into a sealed ϕ 10 mm × 20 mm capsule made by Ti/Zr alloy after being cooled down to room temperature (RT) in a dry furnace.…”
Section: Experiments and Methodsmentioning
confidence: 99%